An abundant ginger compound furanodienone alleviates gut inflammation via the xenobiotic nuclear receptor PXR in mice - Xiaojuan Wang; Guohui Zhang; Zhiwei Bian; Vimanda Chow; Marina Grimaldi; Coralie Carivenc; Savannah Sirounian; Hao Li; Lucia Sladekova; Stefano Mott; Yulia Luperi; Yufeng Gong; et al. (Nature Communications)
Abstract The literature documenting the value of drug-like molecules found in natural products is vast. Although many dietary and herbal remedies have been found to be effective for treating intestinal inflammation, the identification of their active components has lagged behind. In this study, we find that a major ginger component, furanodienone (FDN), is a selective pregnane X receptor (PXR) ligand with agonistic transcriptional outcomes. We show that FDN binds within a sub-pocket of the PXR ligand binding domain (LBD), with subsequent alterations in LBD structure. Using male mice, we show that orally provided FDN has potent PXR-dependant anti-inflammatory outcomes that are colon-specific. Increased affinity and target gene activation in the presence of synergistically acting agonists indicates further opportunities for augmenting FDN activity, efficacy and safety. Collectively, these results support the translational potential of FDN as a therapeutic agent for the treatment and prevention of colonic diseases.